Clinical Liver Disease Progression Among Hepatitis C-Infected Drug Users With CD4 Cell Count Less Than 200 Cells/mm3 Is More Pronounced Among Women Than Men. (31st December 2015) - Baranoski, Amy S.; Cotton, Deborah; Heeren, Timothy; Nunes, David; Kubiak, Rachel W.; Horsburgh, C. Robert
Abstract : The rate of clinical liver disease progression in this cohort of HCV mono-infected and HIV/HCV co-infected individuals was higher than previously reported. Risk of clinical liver disease progression was associated with level of immune suppression, and was more pronounced in women. Abstract: Background.  Hepatitis C virus (HCV) infection is a leading cause of liver-related morbidity and mortality in the United States, and injection drug users are at particularly high risk. Methods.  This prospective observational cohort study assessed the rate of, and risk factors for, clinical liver disease progression in a cohort of HCV monoinfected and human immunodeficiency virus (HIV)/HCV coinfected drug users using unadjusted and multivariate Cox proportional hazards regression analyses. Results.  Of 564 subjects including 421 (75%) with HIV/HCV coinfection and 143 with HCV monoinfection, 55 (10%) had clinical liver disease progression during follow-up with a rate of 25.3 events per 1000 person-years. In unadjusted analysis, there was an interaction between sex and HIV status. In sex-stratified multivariate analysis, HIV/HCV-coinfected women with CD4 <200 cells/mm 3 had 9.99 times the risk of liver disease progression as HCV-monoinfected women (confidence interval [CI], 1.84–54.31; P = .008), and white women had a trend towards increased risk of liver disease progression compared with non-white women (hazard ratio, 2.84; CI, .93–8.68; P = .07). Human immunodeficiency virus/HCV-coinfected men with CD4 <200 cells/mm 3 had 2.86 times the risk of liver disease progression as HCV-monoinfected men (CI, 1.23-6.65; P = .01). Conclusions.  Hepatitis C virus-monoinfected and HIV/HCV-coinfected drug users had high rates of clinical liver disease progression. In those with HIV infection, liver disease progression was associated with advanced immune suppression. This effect was strikingly more pronounced in women than in men.